Pengaruh Kepercayaan Diri dan Keaktifan Berorganisasi terhadap Kemampuan Berbicara di Depan Umum (Public Speaking) Mahasiswa Program Studi Pendidikan Administrasi Perkantoran Universitas Sebelas Maret - Gita Yuliya Widyawati; Tri Murwaningsih; Patni Ninghardjanti (Politeknik Kampar, 2024)
The purpose o this study to determine the effect of (1) the variable self-confidence on the ability to speak in public (public speaking), (2) the variable organizational activeness on the ability to speak in public (public speaking), (3) the variable self-confidence and activeness organization towards public speaking skills. This research was carried out at the Office Administration Education Study Program, Faculty of Teacher Training and Education, Sebelas Maret University. This research is quantitative research with correlational methods. The population in this study was students from the class of 2020 and 2021, totaling 158 people with a total research sample of 113 people. The sample in this research was taken using a purposive sampling technique. The data collection technique used is through questionnaires. The data analysis technique used was multiple linear regression analysis techniques with the help of the SPSS 25.0 for window program. The research results show that: (1) there is a positive and significant effect of the self-confidence variable on public speaking skills as evidenced by a significance value of 0,00 < 0,05 and a tvalue 11,399 > ttable 1,98177; (2) there is a positive and significant effect of the organizational activity variable on public speaking skills as evidenced by a significance value of 0.00 < 0.05 and a tvalue 3,929 > ttable 1,98177; (3) there is a positive and significant effect of the self-confidence variable on public speaking skills as evidenced by a significance value of 0,00 < 0,05 and an Fvalue of 68,101 > Ftable 3,0788. The research results show that the collective effective contribution is 55,3% and the remaining 44,7% is influenced by other variables not included in this research. Thus, the overall results of this analysis support the proposed hypothesis.